More-than-One Health Humans, Animals, and the Environment Post-COVID - Braverman, Irus (Routledge Studies in Environment and Health, 2023)
The call for a One Health approach that transcends species and disciplinary boundaries assumes that human and veterinary medicine are discrete, distinctive domains whose separation must be overcome to achieve health benefits for all. This paper will problematize this assumption by demonstrating that until relatively recently, their boundaries were extremely fluid. Referring to specific examples over the period 1790-1900, it demonstrates that human medicine was once deeply zoological, and encompassed a host of species, practices and social relations that overlapped with those of veterinary medicine. While One Health today focusses selectively on animals as transmitters of zoonotic diseases or as experimental models of human disease, past animal participants in medicine were far more than that. As victims of naturally occurring diseases, they enabled doctors to think generically and comparatively about medical and biological problems, while as disease subjects they encouraged clinical interventions. Their investigation and management could prompt collaboration between doctors and vets. However, veterinary ambitions also encouraged competition. In time, this led to the hardening of boundaries between the professions and their subjects, and subsequent efforts to transcend them under the banner of One Health.